Mn(III)-catalyzed synthesis of pyrroles from vinyl azides and B-keto acids. - Ng, Eileen Pei Jian. (2010)
β-keto acids and vinyl azides are found to be promising precursors for the synthesis of pyrroles with Mn(acac)3 as a catalyst. One electron oxidation of β-keto acids by Mn(acac)3 induces decarboxylation to afford α-keto radicals, which then add on to vinyl azides, leading to the formation of iminyl radicals with elimination of dinitrogen. Intramolecular cyclization of the iminyl radical with a carbonyl moiety gives pyrrole after dehydration with regeneration of the Mn(III) complex.